Effects of caffeine on ethanol-elicited place preference, place aversion and ERK phosphorylation in CD-1 mice. (December 2020) - Porru, Simona; Maccioni, Riccardo; Bassareo, Valentina; Peana, Alessandra T; Salamone, John D; Correa, Mercè; Acquas, Elio
Background: Epidemiological studies indicate a rise in the combined consumption of caffeinated and alcoholic beverages, which can lead to increased risk of alcoholic-beverage overconsumption. However, the effects of the combination of caffeine and ethanol in animal models related to aspects of drug addiction are still underexplored. Aims: To characterize the pharmacological interaction between caffeine and ethanol and establish if caffeine can affect the ability of ethanol (2 g/kg) to elicit conditioned place preference and conditioned place aversion, we administered caffeine (3 or 15 mg/kg) to male CD-1 mice before saline or ethanol. Moreover, we determined if these doses of caffeine could affect ethanol (2 g/kg) elicited extracellular signal-regulated kinase phosphorylation in brain areas, nucleus accumbens, bed nucleus of stria terminalis, central nucleus of the amygdala, and basolateral amygdala, previously associated with this type of associative learning. Results: In the place-conditioning paradigm, caffeine did not have an effect on its own, whereas ethanol elicited significant conditioned-place preference and conditioned-place aversion. Caffeine (15 mg/kg) significantly prevented the acquisition of ethanol-elicited conditioned-place preference and, at both doses, also prevented the acquisition of ethanol-elicited conditioned-place aversion. Moreover, both doses of caffeine also prevented ethanol-elicited extracellular signal-regulated kinase phosphorylation expression in all brain areas examined. Conclusions: The present data indicate a functional antagonistic action of caffeine and ethanol on associative learning and extracellular signal-regulated kinase phosphorylation after an acute interaction. These results could provide exciting grounds for further studies, also in a translational perspective, of their pharmacological interaction modulating other processes involved in drug consumption and addiction.